Identification of plasminogen-binding sites in Streptococcus suis enolase that contribute to bacterial translocation across the blood-brain barrier - Zhao, Tiantong; Gussak, Alex; van der Hee, Bart; Brugman, Sylvia; van Baarlen, Peter; Wells, Jerry M. (Frontiers in Cellular and Infection Microbiology, 2024)
Streptococcus suis is an emerging zoonotic pathogen that can cause invasive disease commonly associated with meningitis in pigs and humans. To cause meningitis, S. suis must cross the blood-brain barrier (BBB) comprising blood vessels that vascularize the central nervous system (CNS). The BBB is highly selective due to interactions with other cell types in the brain and the composition of the extracellular matrix (ECM). Purified streptococcal surface enolase, an essential enzyme participating in glycolysis, can bind human plasminogen (Plg) and plasmin (Pln). Plg has been proposed to increase bacterial traversal across the BBB via conversion to Pln, a protease which cleaves host proteins in the ECM and monocyte chemoattractant protein 1 (MCP1) to disrupt tight junctions. The essentiality of enolase has made it challenging to unequivocally demonstrate its role in binding Plg/Pln on the bacterial surface and confirm its predicted role in facilitating translocation of the BBB. Here, we report on the CRISPR/Cas9 engineering of S. suis enolase mutants eno261, eno252/253/255, eno252/261, and eno434/435 possessing amino acid substitutions at in silico predicted binding sites for Plg. As expected, amino acid substitutions in the predicted Plg binding sites reduced Plg and Pln binding to S. suis but did not affect bacterial growth in vitro compared to the wild-type strain. The binding of Plg to wild-type S. suis enhanced translocation across the human cerebral microvascular endothelial cell line hCMEC/D3 but not for the eno mutant strains tested. To our knowledge, this is the first study where predicted Plg-binding sites of enolase have been mutated to show altered Plg and Pln binding to the surface of S. suis and attenuation of translocation across an endothelial cell monolayer in vitro.